PENINGKATAN KOMPETENSI SISWA SMK MELALUI PELATIHAN ENERGI DASAR SISTEM KELISTRIKAN BERBASIS PRAKTIKUM - Multika Untung Bahagiya; Fulusia Nurmawati; Muhammad Risky (Abdi Masya, 2026)
Digital transformation is projected to be the main driver of change in Indonesia's employment landscape through 2030, with 83% of companies predicting a significant impact on their organizational structure, exceeding the global average of 60%. Field evidence indicates that electric vehicle systems, consisting of electric cars, batteries, inverters, and battery management systems (BMS), are still poorly understood. The purpose of community service is to provide insight and competency to vocational high school students regarding the basic electrical energy systems in cars. The community service activity was carried out at SMK Nurul Huda Jiken. This community service method follows the action research model, consisting of Planning, Implementation, Evaluation, and Reflection. The results of this community service activity showed an average score of 59, which is in the poor category. After participating in the training, participants' abilities increased, with an average score of 92, placing them in the very good ability category. The results of the comparison of the training participants' abilities before and after the activity showed a 30% increase. Therefore, it can be concluded that the competency training of SMK Nurul Huda Jiken students resulted in increased competence and understanding of the basic energy material of the electrical system.